Commercial banking : the management of risk - Gup, Benton E. (John Wiley & Sons, 2005)
'... provides a comprehensive and practical introduction to bank management and to the current banking prctices used to control different kinds of risk ... Written in accordance with current APRA guidelines and regulatory requirements, this text looks beyond Australia to consider the effects on the banking sector of the international financial reporting standards and the new Basel II framework.' --Back cover.